Protocol of a randomized phase II/III study of gemcitabine plus nab-paclitaxel combination therapy versus modified FOLFIRINOX versus S-IROX for metastatic or recurrent pancreatic cancer: JCOG1611 (GENERATE). (16th September 2022) - Mizusawa, Junki; Ohba, Akihiro; Ozaka, Masato; Katayama, Hiroshi; Okusaka, Takuji; Kobayashi, Satoshi; Ikeda, Masafumi; Terashima, Takeshi; Sasahira, Naoki; Okano, Naohiro; Miki, Ikuya; Kaneko, Takashi; et al.
Abstract: Gemcitabine plus nab-paclitaxel and combination chemotherapy with fluorouracil, leucovorin, irinotecan and oxaliplatin are a standard treatment for metastatic or recurrent pancreatic cancer. Recent studies on metastatic pancreatic cancer have demonstrated promising results of modified fluorouracil, leucovorin, irinotecan and oxaliplatin and S-1, irinotecan and oxaliplatin. A three-arm randomized phase II/III trial has been conducted since April 2019 to confirm the superiority of modified fluorouracil, leucovorin, irinotecan and oxaliplatin and S-1, irinotecan and oxaliplatin over Gemcitabine plus nab-paclitaxel in patients with metastatic or recurrent pancreatic cancer. A total of 732 patients will be enrolled from 42 Japanese institutions within 5 years. The primary endpoint is the response rate in the S-1, irinotecan and oxaliplatin arm for phase II portion and overall survival for phase III portion. The secondary endpoints for phase III portion are progression-free survival, response rate, adverse events, serious adverse events and dose intensity. This trial is registered with the Japan Registry of Clinical Trials [https://jrct.niph.go.jp/ ], number jRCTs031190009. Abstract : A randomized phase II/III trial to confirm the superiority of modified fluorouracil, leucovorin, irinotecan and oxaliplatin and S-1, irinotecan and oxaliplatin over Gemcitabine plus nab-paclitaxel in patients with metastatic or recurrent pancreatic cancer was started in April 2019.